Coal, steel, and the rebirth of Europe, 1945 - 1955 the Germans and French from Ruhr conflict to economic community - Gillingham, John R. 1943- (Cambridge Univ. Press, 1991)
John Gillingham: Coal, Steel, and the Rebirth of Europe 1945-1955. The Germans and French from Ruhr Conflict to Economic Community. Cambridge University Press, Cambridge 1991. XV, 397 Seiten, 27,50 englische Pfund